Time-resolved imaging of contrast kinetics magnetic resonance angiography for the assessment of vascular characteristics in intracranial and extracranial tumors in veterinary patients - Hong, Sunghwa; Kim, Soyeon; Yoon, Junghee; Choi, Jihye (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to compare the imaging characteristics and diagnostic utility of Time-Resolved Imaging of Contrast Kinetics (TRICKS) Magnetic Resonance Angiography (MRA) and Computed Tomography Angiography (CTA) for assessing intracranial and extracranial vascular structures in veterinary patients.MethodsThis retrospective methods comparison study included nine client-owned dogs and one cat with head and neck tumors, all of which underwent both CTA and TRICKS MRA. A qualitative assessment of major intracranial and extracranial vessels, as well as tumorassociated vessels—including feeding and draining vessels—was performed. In addition, the signal intensity (SI) of the vessels was quantitatively measured.ResultsBoth imaging techniques provided similar SI measurements, although CTA demonstrated significantly higher SI in the basilar artery. CTA also offered higher visibility and clearer delineation of certain arteries and veins, with a significantly shorter acquisition time. However, TRICKS MRA demonstrated comparable or superior performance in visualizing venous structures and effectively identified tumor-related vessels, showing similar diagnostic performance to CTA in detecting feeding and draining vessels. Additionally, TRICKS exhibited a distinct advantage in differentiating vessels from surrounding bone, effectively reducing bone-related artifacts that can interfere with vascular delineation in CTA.DiscussionTRICKS MRA is a valuable imaging modality for vascular assessment, particularly for evaluating venous structures and tumor-associated circulation. While CTA remains superior for arterial imaging due to its higher spatial resolution and shorter scan time, TRICKS MRA enables dynamic vascular assessment with reduced dependency on contrast injection timing. These findings suggest that TRICKS MRA could serve as a complementary imaging modality in veterinary neuro-oncology, especially for surgical and radiation therapy planning.